Transfusion Practice Patterns in Cancer Patients with Anemia: A Retrospective Study from a Single Oncology Center in Najran, Saudi Arabia - Badheeb, Ahmed; Alotaibi, Bandar; Aman, Abdelaziz; Seada, Islam; Abubakar, Abdullah; Alkarak, Samer; Alramahi, Mohammed; Bazuqamah, Mohammed; Garbo, Ali; Mohammed, Mahran; et al. (Asian Pacific Journal of Cancer Care, 2024)
Background: Recent studies support the safety of restrictive pretransfusion hemoglobulin thresholds (≤7-8 g/dL) for adult cancer patients on chemotherapy. However, the restrictive transfusion strategies role in decreasing inappropriate red blood cell (RBC) transfusion practice in Saudi Arabia is not yet understood. This study aims to evaluate transfusion practices among oncologic patients at Najran Oncologic Center, Saudi Arabia. Materials and Methods: A retrospective chart review study between January 1, 2020, and December 31, 2022, involving 59 adult cancer patients presented to King Khaled Hospital in Najran, Saudi Arabia. Clinical variables for prescribing RBC transfusions based on liberal (> 7 g/dL) or restricted (Hb < 7 g/dL) baseline hemoglobin levels and number of transfused RBCs were investigated in univariate analysis. Results: The mean age was 65.0 ±10.2 years, and most cases were male (n=40, 67.8%). The common primary tumor location was colorectal cancers (n=27, 45.8%), and most cases were in metastatic stages (n=44, 74.6%). The majority of cases (n=36, 61.0%) had severe anemia (Hb < 7 g/dL) at admission. The mean number of RBC units received was 4.9 ±2.4 RBC. Variables associated with restricted prescribing RBC transfusions were male gender (OR: 3.21; 95% CI: 1.05-10.33, p= 0.044), high ECOG-PS status (OR: 2.95; 95% CI: 1.01-9.03, p=0.048), cardiac disease history (OR: 2.05; 95% CI: 0.69-6.44, p= 0.009), and platinum-based chemotherapy (OR: 233.33; 95% CI: 33.12-5054.45, p <0.001). However, survival status was higher among patients with restrictive strategy (OR: 0.25; 95% CI: 0.08-0.73, p= 0.025). Factors associated with an increased number of transfused RBCs were male gender (OR:1.43; 95% CI: 1.07-1.93, p= 0.012), platinum-based chemotherapy (OR:1.55; 95% CI: 1.18-2.15, p= 0.004), history of bleeding (OR: 1.31, 95% CI: 1.02-1.73, p= 0.032), and history of cardiac disease (OR: 1.31 (1.02-1.73; p= 0.002). Conclusion: The study concluded that factors like male gender, platinum-based chemotherapy, bleeding history, and concurrent cardiac disease were associated with an increased number of RBC transfusions. In addition to that, we found a clear adherence to the clinical practice guidelines among the transfused patients. The study suggests an etiology-based approach to cancer-related anemia and transfusions, enabling clinicians to plan safe, targeted therapy and improve patients’ quality of life by synchronizing chemotherapy efficacy.